2017
DOI: 10.3389/fimmu.2017.00752
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Surface Autoantibodies in Neuropsychiatric Disorders: Are There Implications for Depression?

Abstract: Autoimmune diseases are affecting around 7.6–9.4% of the general population. A number of central nervous system disorders, including encephalitis and severe psychiatric disorders, have been demonstrated to associate with specific neuronal surface autoantibodies (NSAbs). It has become clear that specific autoantibodies targeting neuronal surface antigens and ion channels could cause severe mental disturbances. A number of studies have focused or are currently investigating the presence of autoantibodies in spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 144 publications
(175 reference statements)
1
11
0
Order By: Relevance
“…Within this article collection, the role of autoantibodies in “classical” neurodegenerative diseases, such as Parkinson's Disease, is discussed (Jiang et al). This finding contributes to the current observations that autoantibodies to specific neuronal surface antigens are detected in a number of neuropsychiatric disorders (14). Functional validation of these autoantibodies would change the landscape of treatment for a number of neuropsychiatric diseases.…”
Section: Autoimmune Neurological Diseasessupporting
confidence: 79%
“…Within this article collection, the role of autoantibodies in “classical” neurodegenerative diseases, such as Parkinson's Disease, is discussed (Jiang et al). This finding contributes to the current observations that autoantibodies to specific neuronal surface antigens are detected in a number of neuropsychiatric disorders (14). Functional validation of these autoantibodies would change the landscape of treatment for a number of neuropsychiatric diseases.…”
Section: Autoimmune Neurological Diseasessupporting
confidence: 79%
“…Intriguingly, the occurrence of IgG Aabs against neurotransmitter receptors and other macromolecules (DNA, brain lipids, gangliosides, and cardiolipin) has been described in a proportion of SCZ and BPD patients 13 , 14 . Particularly, IgG Aabs against neuronal receptors like N-methyl- d -aspartate receptor (NMDAR), γ-aminobutyric acid receptor (GABAR), and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) have been observed during the psychotic crisis 15 , 16 . Also, a systematic study by Pearlman and Najjar revealed a high prevalence of anti-NMDAR IgG Abs in SCZ patients and to a lesser extent in BPD patients 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Neurotransmitter transporters and receptors are clearly implicated in the pathology of depression and anxiety and they are targeted therapeutically with anti-depressant drugs 13 , 14 . Thus, there is a good reason to consider the possibility that certain NSAbs may constitute one of the putative causes of depression and anxiety 15 17 .…”
Section: Introductionmentioning
confidence: 99%